2020
DOI: 10.3390/md18010054
|View full text |Cite
|
Sign up to set email alerts
|

Recent Discovery of Heterocyclic Alkaloids from Marine-Derived Aspergillus Species

Abstract: Nitrogen heterocycles have drawn considerable attention due to of their significant biological activities. The marine fungi residing in extreme environments are among the richest sources of these basic nitrogen-containing secondary metabolites. As one of the most well-known universal groups of filamentous fungi, marine-derived Aspergillus species produce a large number of structurally unique heterocyclic alkaloids. This review attempts to provide a comprehensive summary of the structural diversity and biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 76 publications
0
24
0
Order By: Relevance
“…The literature search was performed using a previously reported method. [25][26][27][28] The selection of the original articles was of utmost importance because these papers have a direct impact on the findings and the final results. The present review contains all original articles registered with the target subject in the "All Databases" between 2017 and 2020.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search was performed using a previously reported method. [25][26][27][28] The selection of the original articles was of utmost importance because these papers have a direct impact on the findings and the final results. The present review contains all original articles registered with the target subject in the "All Databases" between 2017 and 2020.…”
Section: Literature Searchmentioning
confidence: 99%
“…The previous chemical investigations of N. tabacum indicated that 46 isolated compounds could be divided into nine categories: diterpenoids (1-6), sesquiterpenes (7-13), furan-2-carboxylic acids (14)(15)(16)(17)(18)(19)(20)(21)(22), flavonoids (23)(24)(25)(26)(27)(28)(29)(30)(31)(32), sterols (33-36), 2-arylbenzofurans (37,38), isobenzofurans (39-41), phenylpropanoids (42)(43)(44)(45), and aminoglucoside (46). Among them, terpenes and flavonoids were predominant (Figure 1).…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…Marine-derived fungi that inhabit the marine environment possess the unique metabolic pathways to produce a great diversity of bioactive secondary metabolites, which play an important role in agrochemical and pharmaceutical industries ( Xu et al, 2020 ; Zhang et al, 2020 ). It is well-known that a large number of new marine natural products have been discovered and reported every year ( Carroll et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…11 12 13 14 Thus, the indole alkaloids from marine fungi have drawn considerable attention for their unique chemical structures and significant biological activities. 13 15 16 In the light of the increasing attention paid on the marine fungal indoles, it is necessary to give a comprehensive summary on these indoles from the specific source. Herein, we reviewed the chemical diversity and biological properties of marine fungal indole alkaloids, expecting to provide clear evidence that these metabolites possess potential of application as lead compounds in the drug innovation and discovery.…”
Section: Introductionmentioning
confidence: 99%